The development of mobile & web application for Ricoh photocopier "error code" / Adam Azlan Shah Mohd Salleh - Mohd Salleh, Adam Azlan Shah (2014)
Currently, photocopier service industry is struggling with their technical team to provide efficient service to the customer since they rely on manual physical handbook to progress their services. As we live in advance technology nowadays, there are many technology prospect that can be invented to come up with solutions. Introducing to android mobile application database can store a mountain of information and manual guideline that can ease the technical personnel. It will be a total solution to this matter where the information can be achieved fast and easy at the palm of your hand.